2010
DOI: 10.1002/j.1556-6978.2010.tb00100.x
|View full text |Cite
|
Sign up to set email alerts
|

Social‐Cognitive Development, Ethical and Legal Knowledge, and Ethical Decision Making of Counselor Education Students

Abstract: Counselors are required to have high levels of social-cognitive development, significant knowledge regarding ethical and legal practice, and sound ethical decision-making processes to provide effective and ethical services to their clients. This study investigated the effect of two counseling ethics courses on 64 master's-level counselor education students' levels of social-cognitive development, ethical and legal knowledge, and ethical decision making. Students' ethical and legal knowledge scores increased si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
60
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(69 citation statements)
references
References 29 publications
9
60
0
Order By: Relevance
“…(Lambie et al 2010). Additionally, reliability of the ELICQ with these data was acceptable with an overall alpha coefficient score of .701 (Cohen 1988).…”
Section: Ethical and Legal Issues In Counseling Questionnaire (Elicq)mentioning
confidence: 95%
See 2 more Smart Citations
“…(Lambie et al 2010). Additionally, reliability of the ELICQ with these data was acceptable with an overall alpha coefficient score of .701 (Cohen 1988).…”
Section: Ethical and Legal Issues In Counseling Questionnaire (Elicq)mentioning
confidence: 95%
“…Lambie et al (2010) investigated the effects of a counseling ethics course on counseling students ethical and legal knowledge (as measured by the Ethical and Legal Issues in Counseling Questionnaire [ELICQ]; Lambie et al 2010). They found that the counseling students' ethical and legal knowledge increased significantly upon completion of a 13-week counseling ethics course.…”
Section: Ethical and Legal Knowledgementioning
confidence: 98%
See 1 more Smart Citation
“…Core counselling competencies include how a person relates to him/herself, others and the social environment (Moss et al, 2014). Lambie et al (2010) identified empathy, flexibility, taking alternative perspectives, self-care and emotional wellbeing as key components of effective counselling. The expectation is that counsellors should function on a higher level of emotional wellbeing than their clients to model a way of being for their clients (Corey, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Keywords: Student-Counselor Development, First-Year Experience, Grounded Theory Counselor educators and researchers alike have agreed that gaining insight into one's own progression as a counselor, during the training years and throughout one's own career, is a vital component of healthy counselor development (Donati & Watts, 2005;Lambie, Hagedorn, & Ieva, 2010;Skovholt & Ronnestad, 1992;Woodside, Oberman, Cole, & Carruth, 2007). It is important to identify and examine factors that influence student development because "overlooking these needs and issues can have significant implications for both counselors and the clients they serve" (Furr & Carroll, 2003, p. 39).…”
Section: Editorialmentioning
confidence: 99%